The Application of Videos to Teaching English for Business Communication: EFL Learners’ Perspectives - Duong My Tham, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
The global trends in the 21st century language learning and teaching have promoted interpersonal communication. Recently, there has been a high demand for learning tools which increase learners’ motivation and participation with a focus on communicative competence. This paper aims to explore English majors’ attitudes towards the application of videos in the Business Communication (BC) course at a Vietnamese university. It also explores the students’ favorite learning activities employed during the course. There were 125 third-year English majors participating in the mix-methods research in which both quantitative and qualitative data were collected for an in-depth analysis through the employment of a questionnaire and semi-structured interviews. The findings showed that the participants held a positive attitude (i.e., cognition, emotion, and behavior) toward a video-based Business Communication (VBC) course. As for favourite learning activities, furthermore, collaborative learning activities (e.g., group discussion, role-play, and conversation) tended to be preferred over individual-focused ones (e.g., oral presentation and story-telling).Received 18thAugust 2019; Revised 15thApril 2020; Accepted 20th April 2020